Consumers Satisfaction in Marketing Management: A Conceptual Study - Rusmadi, Rusmadi (International Journal for Educational and Vocational Studies, 2020)
Every business must be attention to customer satisfaction, because satisfaction will have an impact on the sustainability of the business or business. The problem often faced by companies is that companies may not be able to provide maximum satisfaction in accordance with the expectations of consumers or customers. Consumer satisfaction is a major concern for most companies. If the product performance is lower than expectations, the customer will be disappointed; if it turns out as expected, the customer will be satisfied; if it exceeds expectations, the buyer will be very satisfied. This satisfaction will build loyal customers to the product. Every business actor must pay attention to customer satisfaction, because satisfaction will have an impact on the sustainability of the business or business. The problem often faced by companies is that the company may not be able to provide maximum satisfaction in accordance with the expectations of consumers or customers. Consumer satisfaction is a major concern for most companies. If the product performance is lower than expectations, the customer will be disappointed; if it turns out as expected, the customer will be satisfied; if it exceeds expectations, the buyer will be very satisfied. This satisfaction will build loyal customers to the product.